ZAM-CS, a novel chimeric endolysin with enhanced stability and rapid action against methicillin-resistant Staphylococcus aureus - Yasaman Ahmadbeigi; Neda Soleimani; Farzaneh Azizmohseni; Zahra Amini-Bayat (BMC Microbiology)
Abstract Background The rising occurrence of antibiotic resistance in Staphylococcus aureus significantly complicates its treatment. Endolysins are now recognized as a promising substitute for antibiotics in combating multidrug-resistant bacteria. In this research, a novel chimeric endolysin named ZAM-CS was engineered and assessed to achieve enhanced stability, solubility, and rapid bactericidal activity. This was accomplished by combining the catalytic domain of the SAL-1 endolysin with the peptidoglycan binding domain of lysostaphin. Results Expression and purification outcomes indicated that ZAM-CS exhibited significant solubility, with a yield of approximately 23 mg/L. ZAM-CS demonstrated high stability under various temperature conditions and retained most of its activity in both acidic and alkaline pH. The results of turbidity reduction assay showed a 50% decrease in the initial OD600 within 10 min at a minimum concentration of 2 µg/mL. The minimum inhibitory concentration and the minimum bactericidal concentration values of ZAM-CS are identical in the methicillin-resistant Staphylococcus aureus strain, indicating the strong bactericidal properties of this endolysin. Antimicrobial tests showed ZAM-CS was also effective against coagulase-negative Staphylococci, Streptococcus agalactiae, and Enterococcus faecalis. Conclusion The rapid and dynamic action and high stability of ZAM-CS compared to other recombinant endolysins make it a suitable candidate for development to replace antibiotics targeting harmful Staphylococci, including MRSA.